On reducibility of linear De-system with constant coefficients on the diagonal to De-system with Jordan matrix in the case of equivalence of its higher order one equation - Kulzhumiyeva, A.A.; Sartabanov, Zh.A. (Bulletin of the Karaganda University. Mathematics Series, 2016)
In article proposed the method of bringing a linear system with constant coeficients on the diagonal to canonical form under some conditions on the own values of the system. Using this method, you can examine the structure and (θ, ω, ω)-periodic solutions of linear systems of equations with diferential operator on the main diagonal.